2001
DOI: 10.1002/hpm.630
|View full text |Cite
|
Sign up to set email alerts
|

The demand for child curative care in two rural thanas of Bangladesh: effect of income and women's employment

Abstract: This paper seeks to investigate the determinants of child health care seeking behaviours in rural Bangladesh. In particular, the effects of income, women's access to income, and the prices of obtaining child health care are examined. Data on the use of child curative care were collected in two rural areas of Bangladesh--Abhoynagar Thana of Jessore District and Mirsarai Thana of Chittagong District--in March 1997. In estimating the use of child curative care, the nested multinomial logit specification was used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Only 36% of the studies were randomized trials. Of the 25 studies, 13 were in South America or the Caribbean [7,8,10,25,26,34,43-45,47-49,51], 8 were in Africa [15,16,33,40,42,50,52,53] and 4 were in South East Asia [21-23,46]. 48% of the studies evaluated cash transfer programs: 41% evaluated conditional cash transfer programs and 7% evaluated unconditional cash transfer programs.…”
Section: Resultsmentioning
confidence: 99%
“…Only 36% of the studies were randomized trials. Of the 25 studies, 13 were in South America or the Caribbean [7,8,10,25,26,34,43-45,47-49,51], 8 were in Africa [15,16,33,40,42,50,52,53] and 4 were in South East Asia [21-23,46]. 48% of the studies evaluated cash transfer programs: 41% evaluated conditional cash transfer programs and 7% evaluated unconditional cash transfer programs.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have suggested that urbanization may decrease healthcare gender inequalities [42]. Accessibility of the physician in urban areas is made possible by several factors: 1) higher urban physician (especially female physician) population density ratios 2) reduced travel time to healthcare facilities 3) superior transportation infrastructure 4) denser populations with stronger social support networks that maintain purdah without restricting mobility [11,12,43,44]. Developing effective health policy to manage the chronic disease epidemic must take precautions to protect vulnerable groups and address the challenges they face accessing care.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include the availability, accessibility, and quality of services as well as the characteristics of the users and communities in which the users live. Specifically, these may include distance to health service, cost of services, technical qualifications of health practitioners, socioeconomic status of the users, and women's autonomy in household decision-making [20-23]. Studies from rural Bangladesh found that some of these factors were positively associated with the utilization of health services [13-15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from rural Bangladesh found that some of these factors were positively associated with the utilization of health services [13-15,18,19]. However, many of these studies were based on a limited number of factors and focused on either preventive or curative modern health care services in small geographical areas [13-15,18,19,23-26]. As a result, they neither examined the net effects of a wider set of individual, community, and provider-level factors nor did they cover rural areas from different regions to see how the recent increase in the availability of maternal and child health services was affecting utilization by different socioeconomic groups [13-19,23-26].…”
Section: Introductionmentioning
confidence: 99%